دور نظم المعلومات التسويقية في تحسين جودة الخدمة بمؤسسات النقل الجماعي دراسة حالة شركة النقل بالسكك الحديدية -سوق اهراس- - منال بوقرة; نصيرة فجيري (My University, 2022)
This study aims to clarify the role of the marketing information system in improving the quality of service in the public transport sector through the theoretical treatment of concepts related to marketing information systems in improving the quality of service, especially in light of the current developments related mainly to the information revolution. Marketing information and its processing and to benefit from it and use it in making decisions and improving the quality of service that enables it to be distinguished. That is why we tried in this study to shed light on these concepts related to the marketing information system, as well as concepts related to service quality, its dimensions and methods of improving it. It was distributed over a sample of 40 ribs, and then we analyzed its results using the spas program. The study reached many results, the most important of which are: The marketing information system has an effective role in improving service quality. ......................................... تهدف هذه الدراسة إلى توضيح دور نظام المعلومات التسويقية في تحسين جودة الخدمة بقطاع النقل العمومي بالجرائر و ذلك من خلال المعالجة النظرية للمفاهيم المتعلقة بنظم المعلومات التسويقية في تحسين جودة الخدمة و خاصة في ظل التطورات الراهنة و المتعلقة أساسا بثورة ألمعلومات فقد زاد اهتمام المؤسسات ببنائها وذلك لتوفير المعلومات التسويقية و معالجتها وللاستفادة منه و توظيفها في اتخاذ القرارات وتحسين جودة الخدمة التي تمكنها من التميز. لهذا حاولنا في هذه الدراسة إلقاء الضوء على هذه المفاهيم المتعلقة بنظام المعلومات ألتسويقية و كذا المفاهيم المتعلقة بجودة الخدمة و أبعادها و أساليب تحسينها، حيث قمنا بإسقاط نتائج الدراسة النظرية على شركة النقل بالسكك الحديدية بولاية سوق أهراس معتمدين في ذلك على استمارة موجهة لعملاء ألمؤسسة .spas حيث تم توزيعها على عينة متمثلة في 40 ربون ثم قمنا بتحليل نتائجها باستخدام برنامج وقد توصلت الدراسة إلى العديد من النتائج لعل أهمها: إن نظام المعلومات التسويقية له دور فعال في تحسين جودة الخدمة